EFFECT OF CORE HEIGHT ON GENERAL STABILITY OF HONEYCOMB SANDWICH STRUCTURE - JIN Di; QIAO LingYun; FAN Yu (Jixie qiangdu, 2017)
Buckling loads of honeycomb sandwich structure under compression and shear load was calculated by engineering algorithm and finite element method. Stability test on specimens was conducted to obtain buckling loads. The test results also verified the accuracy of the finite element method. The effect of core height on general stability problem of honeycomb sandwich structure for thin composite panels was discussed. The results show that it is increasing core height that could enhance flexure strength of composite honeycomb sandwich structure,but the spare carrying capacity descends. The strain of panels increases and indeed to exceed the allowable with only increasing core height.